2017
DOI: 10.1080/13102818.2017.1316684
|View full text |Cite
|
Sign up to set email alerts
|

Sukkularetrotransposon movements in the human genome

Abstract: Retrotransposons, a subclass of mobile genetic elements, have been discovered in many organisms. In this study, we identified a plant-specific retrotransposon (Sukkula) in the human genome (24 different DNA samples) by using retrotransposon-based molecular marker technique: interretrotransposon amplified polymorphism. There were five different groups related to the ages of the subjects. The polymorphism ratios were 8%-100% among all samples, 10%-91% among females (12 subjects) and 13%-100% among males (12 subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The study conducted by Elkina and colleagues have shown that SIRE1 and BARE-1 are present in the genome of farm animals and have different distribution within genomes. In the previous study of our research group, we determined SIRE1 retrotransposon in the human genome (Cakmak et al, 2017). Table 1 Another study conducted by Metzger and colleagues stated that a selfish endogenous retroelement "Steamer" belonged to soft-shell clam family, also founded within the genome of 19 different bivalve species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study conducted by Elkina and colleagues have shown that SIRE1 and BARE-1 are present in the genome of farm animals and have different distribution within genomes. In the previous study of our research group, we determined SIRE1 retrotransposon in the human genome (Cakmak et al, 2017). Table 1 Another study conducted by Metzger and colleagues stated that a selfish endogenous retroelement "Steamer" belonged to soft-shell clam family, also founded within the genome of 19 different bivalve species.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, barley retrotransposons such as BARE-1, Sukkula and SIRE1 have been shown to have active homologues in genomes of other cereals (Bonchev & Parisod, 2013;Cakmak et al, 2015;Cakmak et al, 2017). Recent studies have shown existence of plant retrotransposons in animals (Elkina et al, 2015;Cakmak et al, 2017). The study conducted by Elkina and colleagues have shown that SIRE1 and BARE-1 are present in the genome of farm animals and have different distribution within genomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed barley specific retrotransposons in endemic Colchium chalcedonicum (Karlık et al, 2019). Recently we were able to find barley specific retrotransposons in human genome (Cakmak et al, 2017. We also tested retrotransposon movements for short term mutagenicity test (Yilmaz et al, 2018).…”
Section: Our Research With Transposonsmentioning
confidence: 99%
“…Therefore, LTR primers designed according to a species can be used to amplify DNA of others. As a result, IRAP gives very valuable information related to the genomes of different species [15,16].…”
Section: Introductionmentioning
confidence: 99%